Concentration effects on spontaneous and amplified emission in benzo[c]fluorenes1. Issue 19 (21st May 2015) - Kazlauskas, Karolis; Kreiza, Gediminas; Radiunas, Edvinas; Adomėnas, Povilas; Adomėnienė, Ona; Karpavičius, Karolis; Bucevičius, Jonas; Jankauskas, Vygintas; Juršėnas, Saulius
<x xml:space="preserve">Abstract</x> Deep-blue-emitting benzo[c]fluorenes with suppressed concentration quenching of emission enabled to attain the lowest amplified emission threshold in the neat amorphous films under ambient conditions.